Negative electrode active material for lithium ion battery as well as preparation method and application of negative electrode active material

By adopting a multi-layer carbon-covered structure in the negative electrode material of lithium-ion battery, the structural failure and performance attenuation problems caused by volume changes in the silicon carbon negative electrode material during charging and discharging are solved, and higher battery performance and longer cycle life are achieved.

CN119601625AActive Publication Date: 2025-03-11SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411730206.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The volume of silicon carbon anode material changes greatly during the charging and discharging process of lithium-ion batteries, resulting in damage to the electrode structure, peeling of active substances and decomposition of electrolytes, resulting in rapid attenuation of capacity and shortening of cycle life.

Method used

Multi-layer carbon-coated structures are adopted, including nanoporous silicon materials, nitrogen-doped and/or sulfur-doped conductive carbon material coatings, boron-doped graphitized carbon material coatings, amorphous and crystalline carbon hybrid coatings, and inorganic oxide or LiPON protective layers. The conductive, structural stability and ion transport capability of the material are improved through the synergy of these layers.

Benefits of technology

It significantly improves the first Coulomb efficiency, rate performance and high-temperature cycling performance of lithium-ion batteries, extends the cycle life of the battery, and improves the heat conduction performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601625A_ABST
    Figure CN119601625A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material for a lithium ion battery as well as a preparation method and application of the negative electrode material. The negative electrode active material for the lithium ion battery comprises a nano porous silicon material, a first carbon coating layer, a second carbon coating layer, a third carbon coating layer and a protective layer, the first carbon coating layer, the second carbon coating layer, the third carbon coating layer and the protective layer sequentially coat the nano porous silicon material, and the first carbon coating layer is formed by a nitrogen and / or sulfur doped conductive carbon material. The binding force of the first carbon coating layer and the nano-porous silicon material at the interface of the first carbon coating layer and the nano-porous silicon material is 15-25MPa; the second carbon coating layer is formed by a boron-doped graphitized carbon material, and the graphitization degree coefficient of the graphitized carbon material is 0.6-0.9; the third carbon coating layer contains 30 to 50 wt% of amorphous carbon and 50 to 70 wt% of crystalline carbon. The lithium ion battery formed by adopting the negative electrode material has excellent first coulombic efficiency, capacity retention ratio and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy technology, and specifically relates to a negative electrode active material for lithium ion batteries and a preparation method and application thereof. Background Art

[0002] Silicon-carbon anode materials are considered to be ideal candidate materials for the next generation of lithium-ion batteries due to their high specific capacity and good cycle performance. However, the silicon in silicon-carbon anode materials undergoes a huge volume change during the charge and discharge process, which can reach 300%, leading to problems such as electrode structure destruction, active material peeling, and continuous decomposition of the electrolyte, resulting in rapid battery capacity decay and shortened cycle life.

[0003] To solve this problem, researchers have proposed a variety of carbon coating strategies to improve the performance of silicon-based negative electrode materials. Traditional carbon coating methods mainly include liquid phase carbon coating, gas phase carbon coating, etc. However, it is often difficult for a single carbon coating to be formed on the surface of a silicon-based negative electrode so that the negative electrode material has the comprehensive requirements of conductivity, stability, and mechanical strength. For example, the carbon layer formed in the prior art is usually not uniform and compact enough, and it is difficult to effectively alleviate the volume expansion of the silicon material. Or the quality of the carbon layer is unstable, and pores and cracks are easily generated, which cannot effectively protect the silicon material. In addition, silicon-carbon negative electrode materials are prone to side reactions with the electrolyte during long-term cycles to form an unstable solid electrolyte interface (SEI) film, which affects its long-term stability.

[0004] Therefore, there is an urgent need to develop a high-performance lithium-ion battery anode material to meet the growing performance requirements of the next generation of high-energy-density lithium-ion batteries for anode materials. Summary of the invention

[0005] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:

[0006] The present invention provides a negative electrode active material for a lithium ion battery, comprising:

[0007] Nanoporous silicon materials;

[0008] A first carbon coating layer, which is formed of a conductive carbon material doped with nitrogen and / or sulfur and coated on the nanoporous silicon material, and at least part of the N atoms and / or S atoms in the first carbon coating layer are chemically bonded to at least part of the Si atoms in the nanoporous silicon material at the interface between the first carbon coating layer and the nanoporous silicon material; according to a nanoindentation test method, the binding force between the first carbon coating layer and the nanoporous silicon material at the interface between the two is 15-25 MPa;

[0009] A second carbon coating layer is formed of a boron-doped graphitized carbon material and coated on the first carbon coating layer; according to Raman spectroscopy, the graphitization degree coefficient of the graphitized carbon material is 0.6 to 0.9;

[0010] a third carbon coating layer comprising 30-50 wt% amorphous carbon and 50-70 wt% crystalline carbon, coated on the second carbon coating layer, wherein the amorphous carbon and the crystalline carbon are uniformly mixed and distributed;

[0011] The protective layer includes one or more of inorganic oxides, inorganic fluorides or LiPON (lithium phosphorus oxygen nitrogen) and is coated on the third carbon coating layer.

[0012] Among them, in the method for calculating the degree of graphitization coefficient according to Raman spectroscopy, the degree of graphitization coefficient R = IG / (IG+ID), IG and ID are the integrated intensities of the G peak and the D peak in the Raman spectrum, respectively. 1 ) represents graphite structure, D peak (about 1350cm- 1 ) represents defects or disordered structures. The higher the degree of graphitization, the closer the R value is to 1.

[0013] In the negative electrode active material provided by the present invention, the first carbon coating layer forms a strong interaction with the silicon surface through the rich functional groups on the conductive carbon material, provides excellent interface bonding force, effectively prevents the carbon coating layer from falling off during the cycle, and maintains the structural integrity of the material; the graphitized structure of the second carbon coating layer provides good mechanical strength, and boron doping introduces additional electron carriers to improve the conductivity of the carbon layer. The second carbon coating layer can enhance the conductive network of the entire electrode and accelerate electron transmission, while providing mechanical support and inhibiting the volume expansion of the silicon material; the amorphous carbon in the third carbon coating layer provides flexibility and porosity, and the crystalline carbon provides high conductivity. The formed "soft and hard" structure has good buffering capacity, can absorb the stress generated by the volume change of the silicon material and prevent the material from cracking, and can also maintain high conductivity to ensure rapid electron transmission.

[0014] Due to the synergistic effect of the strong interfacial bonding force of the first carbon coating layer and the high conductivity of the second carbon coating layer, the negative electrode active material can maintain a stable electron transport network in long-term cycles; and the negative electrode active material also has both flexible buffering and rigid support, and the amorphous carbon in the third carbon coating layer cooperates with the graphite structure of the second coating layer to provide a buffering effect while maintaining the overall structural stability; the negative electrode active material also has a multi-scale pore structure, and the three layers of carbon coating together construct a multi-scale pore network from micro to macro, which is conducive to the penetration of electrolyte and the rapid transmission of lithium ions. The present invention finds that the three-layer carbon coating of the above structure also helps to form a more stable and uniform SEI film, reducing the irreversible capacity loss of the battery; and improves the thermal conductivity of the material, which helps to better manage heat during high-rate charging and discharging.

[0015] In some embodiments, the specific surface area of ​​the nanoporous silicon material is 800 to 1200 m 2 / g.

[0016] In some embodiments, the nanoporous silicon material has a three-dimensional interconnected pore structure, and the pores contained in the three-dimensional interconnected pore structure have a pore size of 10N30nm.

[0017] In some embodiments, the thickness ratio of the first carbon coating layer, the second carbon coating layer, and the third carbon coating layer is (2-3):(5-10):(5-8).

[0018] In some preferred embodiments, the thickness of the first carbon coating layer is 2-3 nm, the thickness of the second carbon coating layer is 5-10 nm, and the thickness of the third carbon coating layer is 5-8 nm.

[0019] In some embodiments, the protective layer has a thickness of 1-5 nm.

[0020] In some embodiments, the median particle size D50 of the negative electrode active material for lithium-ion batteries is 1 to 10 um.

[0021] In some embodiments, the conductive carbon material includes one or more of dopamine, polypyrrole or polythiophene.

[0022] In some embodiments, the boron doping amount in the second carbon coating layer is 0.2-2 wt %.

[0023] In some embodiments, the third carbon coating layer is formed by carbonizing a mixture of soft pitch and hard pitch at 600-1000°C.

[0024] In some embodiments, the inorganic oxide includes one or more of Al2O3, TiO2, and ZrO2, and the inorganic fluoride includes AlF3.

[0025] A second object of the present invention is to provide a method for preparing the negative electrode active material for a lithium ion battery as described in any one of the above items, comprising:

[0026] Using a nitrogen and / or sulfur-doped conductive carbon material to perform liquid-phase carbon coating on a nanoporous silicon material to form a first carbon coating layer on the surface of the nanoporous silicon material to obtain a first intermediate material;

[0027] Using a gaseous carbon source to perform chemical vapor deposition on the first intermediate material, and introducing a boron source during the chemical vapor deposition process to form a boron-doped graphitized carbon material on the surface of the first carbon coating layer to form a second carbon coating layer, thereby obtaining a second intermediate material;

[0028] Allowing the surface of the second intermediate material to adsorb a carbon precursor, and carbonizing the second intermediate material adsorbing the carbon precursor to convert the carbon precursor into amorphous carbon and crystalline carbon to form a third carbon coating layer, thereby obtaining a third intermediate material;

[0029] At least one or more of inorganic oxides, inorganic fluorides or LiPON is deposited on the surface of the third intermediate material using atomic layer deposition technology to form a protective layer to obtain a negative electrode material for a lithium ion battery.

[0030] In some embodiments, the preparation method specifically includes: immersing the nanoporous silicon material in a solution containing 0.1 to 20 mg / mL of nitrogen and / or sulfur-doped conductive carbon material, reacting at a temperature of 60 to 80° C. for 4 to 8 hours to obtain the first intermediate material.

[0031] In some embodiments, the nitrogen and / or sulfur-doped conductive carbon material includes one or more of dopamine, polypyrrole or polythiophene.

[0032] In some embodiments, the chemical vapor deposition temperature is 600-1000° C., and the time is 2-30 hours.

[0033] In some embodiments, the gaseous carbon source includes acetylene and / or methane.

[0034] In some preferred embodiments, the gaseous carbon source includes acetylene and methane in a volume ratio of 2-4:1-2.

[0035] In some embodiments, the boron source includes triethylboron.

[0036] In some embodiments, the amount of the boron source introduced is 1-5 wt % of the gaseous carbon source.

[0037] In some embodiments, the preparation method specifically includes: dispersing the carbon precursor in a solvent to obtain a solution containing 3 to 30 wt% of the carbon precursor, and immersing the second intermediate material in the solution for 12 to 48 hours so that the carbon precursor is adsorbed on the surface of the second intermediate material; and carbonizing at a temperature of 600 to 1000°C for 2 to 4 hours to obtain the third intermediate material.

[0038] In some embodiments, the carbon precursor includes one or more combinations of soft asphalt, glucose, sucrose, starch, hard asphalt, phenolic resin, and furan resin.

[0039] In some preferred embodiments, the carbon precursor includes soft pitch and hard pitch.

[0040] The method of using the atomic layer deposition technology to deposit one or more of inorganic oxides, inorganic fluorides or LiPON on the surface of the third intermediate material to form a protective layer can adopt any existing method, and the present invention does not impose any particular limitation on this.

[0041] The third object of the present invention is to provide a negative electrode for a lithium ion battery, the negative electrode for the lithium ion battery comprising a negative electrode collector and a negative electrode active material layer formed on the negative electrode collector, the negative electrode active material layer being any one of the negative electrode materials for a lithium ion battery described.

[0042] A fourth object of the present invention is to provide a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is the negative electrode of the lithium ion battery.

[0043] Compared with the prior art, the present invention has at least the following beneficial effects: the porous silicon material in the negative electrode active material provided by the present invention can effectively alleviate the volume expansion during the charge and discharge process and provide abundant ion channels; the multi-layer carbon coating structure can improve the conductivity of the material, enhance the interface bonding force, and optimize the carbon structure; the outer protective layer can provide uniform and dense surface protection for the material; through the synergistic effect between the layers, the multi-layer synergy realizes the comprehensive improvement of the conductivity, structural stability, ion transmission capacity and surface protection performance of the negative electrode active material; compared with the single carbon-coated negative electrode material, the negative electrode material provided by the present invention can increase the first coulomb efficiency of the lithium ion battery by 10-15%, the rate performance by more than 50%, and the performance attenuation in the high-temperature cycle of 60°C is reduced by 40%; the capacity retention rate of the negative electrode material after 1000 cycles reaches more than 92%, and the capacity is still maintained at more than 80% under a large current of 10C. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 is a SEM image of the negative electrode active material prepared in one embodiment of the present invention;

[0046] Figure 2 is a multi-layer cross-sectional view of a negative electrode active material prepared in one embodiment of the present invention;

[0047] Figure 3 1 is an XRD diagram of the negative electrode active material prepared in one embodiment of the present invention. DETAILED DESCRIPTION

[0048] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0049] Unless otherwise specified, in the specific embodiments of the present invention, various raw materials, reagents, reaction equipment, and testing equipment used can be obtained through commercial purchase and other channels, and the testing method is a conventional method in the art.

[0050] Example 1

[0051] Embodiment 1 provides a negative electrode material for a lithium ion battery and a preparation method thereof, which specifically comprises the following steps:

[0052] Preparation of nanoporous silicon material: NaCl particles were used as sacrificial templates, silane gas was pyrolyzed at 550°C to deposit on the surface of NaCl particles, and then the NaCl template was removed by water dissolution to obtain a nanoporous silicon material with a three-dimensional interconnected pore structure; the pore size of the nanoporous silicon material was found to be about 20nm, and the specific surface area reached 1000m 2 / g;

[0053] The prepared nanoporous silicon material was immersed in a 2 mg / mL dopamine solution and reacted at 60° C. for 6 hours under a pH of 8.5 to form a 2.5 nm thick dopamine carbon layer on the surface of the porous silicon material, which was recorded as the first intermediate material. The binding force between the dopamine carbon layer and the nanoporous silicon material at the interface was measured by a nanoindentation test method to be approximately 17 MPa.

[0054] The first intermediate material is placed in a tube furnace at 800° C., and a mixed gas of acetylene and methane (volume ratio 3:1) is introduced therein, and 0.5 wt % of triethyl boron is introduced for chemical vapor deposition, and the reaction is carried out for 30 minutes to form a 7 nm thick boron-doped graphitized carbon layer on the surface of the first intermediate material, which is recorded as the second intermediate material; according to the Raman spectroscopy method, the graphitization degree coefficient of the boron-doped graphitized carbon layer is 0.67;

[0055] Soft asphalt and hard asphalt are mixed in a mass ratio of 1:1 and dissolved in tetrahydrofuran to obtain a tetrahydrofuran solution of asphalt with a concentration of 20wt%, and the second intermediate material is immersed in the solution for 36 hours, then filtered and carbonized at 800°C for 2 hours, and a 6nm thick mixed asphalt carbon layer is formed on the second intermediate material, which is recorded as the third intermediate material; XRD fitting peak detection shows that the mixed asphalt layer contains 27wt% amorphous carbon and 73wt% crystalline carbon;

[0056] Atomic layer deposition technology is used, with trimethylaluminum and water as precursors, and 20 cycles of deposition are performed at a temperature of 200°C to form a 2nm thick Al2O3 protective layer on the third intermediate material to obtain a negative electrode material.

[0057] Figure 1 is a SEM image of the negative electrode active material prepared in this example, Figure 2 is a multi-layer cross-sectional view of the negative electrode active material prepared in this embodiment, Figure 3 is the XRD pattern of the negative electrode active material prepared in this example.

[0058] Example 2

[0059] Embodiment 2 provides a negative electrode material for a lithium ion battery and a preparation method thereof, which specifically comprises the following steps:

[0060] Preparation of nanoporous silicon material: Porous silicon was prepared by magnesium thermal reduction method. SiO2 and magnesium powder were mixed in a molar ratio of 1:2, reacted at 650°C for 4 hours, and then washed with hydrochloric acid to remove MgO to obtain nanoporous silicon material. The pore size of the nanoporous silicon material was 15nm and the specific surface area was 950m 2 / g;

[0061] The prepared nanoporous silicon material is dispersed in a 0.1 mol / mL pyrrole monomer solution, and an oxidant ammonium persulfate with a concentration of 0.05 mol / L is added, and the mixture is reacted at room temperature for 8 hours to form a 3 nm thick polypyrrole layer on the surface of the nanoporous silicon material, which is recorded as the first intermediate material; the binding force between the dopamine carbon layer and the nanoporous silicon material at the interface is measured by a nanoindentation test method to be about 17 MPa;

[0062] The first intermediate material is placed in a tube furnace at 850° C., and a mixed gas of acetylene and methane (volume ratio 3:1) is introduced therein, and 0.6 wt % of triethyl boron is introduced for chemical vapor deposition for 25 minutes to form a 10 nm thick boron-doped graphitized carbon layer on the surface of the first intermediate material, which is recorded as the second intermediate material; according to the Raman spectroscopy method, the graphitization degree coefficient of the boron-doped graphitized carbon layer is 0.79;

[0063] Soft asphalt and hard asphalt are mixed in a mass ratio of 1:1 and dissolved in tetrahydrofuran to obtain a 20wt% asphalt tetrahydrofuran solution, the second intermediate material is immersed in the solution for 48 hours, and then filtered, and then carbonized at 600°C for 3 hours to form an 8nm thick mixed asphalt layer on the second intermediate material, which is recorded as the third intermediate material; XRD fitting peak detection shows that the mixed asphalt layer contains 26wt% amorphous carbon and 74wt% crystalline carbon;

[0064] Atomic layer deposition technology is used, with titanium tetrachloride and water as precursors, and 25 cycles of deposition are performed at a temperature of 180°C to form a 1nm thick TiO2 protective layer on the third intermediate material to obtain a negative electrode material.

[0065] Example 3

[0066] Embodiment 1 provides a negative electrode material for a lithium ion battery and a preparation method thereof, which specifically comprises the following steps:

[0067] Preparation of nanoporous silicon material: NaCl particles were used as sacrificial templates, silane gas was pyrolyzed at 550°C to deposit on the surface of NaCl particles, and then the NaCl template was removed by water dissolution to obtain a nanoporous silicon material with a three-dimensional interconnected pore structure; the pore size of the nanoporous silicon material was found to be about 20nm, and the specific surface area reached 1000m 2 / g;

[0068] The prepared nanoporous silicon material was immersed in a 20 mg / mL thiophene solution, and after being evenly dispersed, 10 ml of a 2 mg / mL ferric chloride solution was added dropwise, fully stirred, and reacted at 80° C. for 4 hours to form a 2 nm thick polythiophene carbon layer on the surface of the porous silicon material, which was recorded as the first intermediate material; the binding force between the polythiophene carbon layer and the nanoporous silicon material at the interface was measured by a nanoindentation test method to be approximately 18 MPa;

[0069] The first intermediate material is placed in a tube furnace at 1000° C., and a mixed gas of acetylene and methane (volume ratio 3:1) is introduced therein, and 0.5 wt % of triethyl boron is introduced for chemical vapor deposition, and the reaction is carried out for 30 minutes to form a 5 nm thick boron-doped graphitized carbon layer on the surface of the first intermediate material, which is recorded as the second intermediate material; according to the Raman spectroscopy method, the graphitization degree coefficient of the boron-doped graphitized carbon layer is 0.73;

[0070] Soft asphalt and hard asphalt are mixed in a mass ratio of 1:1 and dissolved in tetrahydrofuran to obtain an asphalt tetrahydrofuran solution with a concentration of 20wt%, and the second intermediate material is immersed in the solution for 12 hours, then filtered and carbonized at 600°C for 4 hours, and a 5nm thick mixed asphalt carbon layer is formed on the second intermediate material, which is recorded as the third intermediate material; XRD fitting peak detection shows that the mixed asphalt layer contains 21wt% amorphous carbon and 79wt% crystalline carbon;

[0071] Atomic layer deposition technology is used, with trimethylaluminum and water as precursors, and 20 cycles of deposition are performed at a temperature of 200°C to form a 5nm thick ZrO2 protective layer on the third intermediate material to obtain a negative electrode material.

[0072] Example 4

[0073] Example 4 is basically the same as Example 1, except that the protective layer of Example 4 is AlF3.

[0074] Example 5

[0075] Embodiment 5 is substantially the same as Embodiment 1, except that the protective layer of Embodiment 5 is LiPON.

[0076] Comparative Example 1

[0077] The only difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not form a dopamine carbon layer, that is, a boron-doped graphitized carbon layer, a mixed asphalt carbon layer and an Al2O3 protective layer are directly coated on the surface of the nanoporous silicon material in sequence, and the rest is implemented in the same way as Example 1.

[0078] Comparative Example 2

[0079] The only difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not form a boron-doped graphitized carbon layer, that is, a dopamine carbon layer, a mixed asphalt carbon layer and an Al2O3 protective layer are sequentially coated on the surface of the nanoporous silicon material, and the rest is implemented in the same way as Example 1.

[0080] Comparative Example 3

[0081] The only difference between Comparative Example 3 and Example 1 is that Comparative Example 3 does not form a mixed asphalt carbon layer, that is, a dopamine carbon layer, a boron-doped graphitized carbon layer and an Al2O3 protective layer are sequentially formed on the surface of the nanoporous silicon material, and the rest is implemented in the same way as Example 1.

[0082] Comparative Example 4

[0083] The only difference between Comparative Example 4 and Example 1 is that Comparative Example 4 does not form a protective layer, that is, a dopamine carbon layer, a boron-doped graphitized carbon layer and a mixed asphalt carbon layer are sequentially formed on the surface of the nanoporous silicon material, and the rest is implemented in the same way as Example 1.

[0084] Comparative Example 5

[0085] The only difference between Comparative Example 5 and Example 1 is that the thicknesses of the dopamine carbon layer, the boron-doped graphitized carbon layer, and the mixed asphalt carbon layer in Comparative Example 5 are 2.5 nm, 7 nm, and 12 nm, respectively, and the method is implemented in the same manner as Example 1. The present invention finds that when the thickness of the mixed asphalt carbon layer is thicker, the overall performance of the battery decreases, which is specifically reflected in the decrease in the first efficiency of the battery and the acceleration of the side reactions on the surface of the high-temperature cycle. This may be due to the presence of more active sites in the amorphous carbon in the graphite carbon layer, which promotes the decomposition of the electrolyte to generate more SEI layers, consumes active lithium ions, and causes the side reactions to deepen.

[0086] Comparative Example 6

[0087] The only difference between Comparative Example 6 and Example 1 is that the thicknesses of the dopamine carbon layer, the boron-doped graphitized carbon layer, and the mixed asphalt carbon layer in Comparative Example 6 are 2.5 nm, 15 nm, and 6 nm, respectively, and the method is the same as that of Example 1. The present invention finds that when the thickness of the boron-doped graphitized carbon layer is thicker, the overall performance of the battery decreases, which is specifically reflected in the decrease in capacity. This is because although the boron-doped graphitized carbon layer has good ionic conductivity, its capacity is relatively low, and the increase in thickness leads to a decrease in capacity.

[0088] Comparative Example 7

[0089] The only difference between Comparative Example 7 and Example 1 is that the thicknesses of the dopamine carbon layer, the boron-doped graphitized carbon layer, and the mixed asphalt carbon layer in Comparative Example 7 are 6 nm, 7 nm, and 6 nm, respectively, and the implementation is the same as Example 1. The present invention finds that when the thickness of the dopamine carbon layer is thicker, the overall performance of the battery decreases, which is specifically reflected in the decrease of the cycle and high-temperature storage performance. This may be because the residual N and H elements in the dopamine carbon layer will increase the consumption of the electrolyte, especially under high-temperature storage conditions, excessive consumption of the electrolyte leads to loss of active lithium and increase of irreversible capacity.

[0090] The negative electrode active materials in the above embodiments and comparative examples are used to prepare the negative electrode of a lithium ion battery, specifically including the following:

[0091] (1) Positive electrode preparation: The positive electrode is lithium nickel cobalt manganese oxide (NCM523, LiNi 0.5 C o0.2 Mn 0.3 O2) material. NCM523, conductive agent (super P) and binder (PVDF) were mixed in a mass ratio of 92:4:4, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred to form a slurry; the slurry was evenly coated on an aluminum foil current collector, and then compacted after vacuum drying at 80°C for 12 hours to obtain a positive electrode sheet; the area specific capacity of the positive electrode was 3.5 mAh / cm 2 ;

[0092] (2) Preparation of negative electrode: The negative electrode material, graphite conductive agent and binder CMC-SBR prepared in the above embodiment or comparative example were mixed in a mass ratio of 80:10:10, deionized water was added, and the mixture was stirred to form a slurry; the slurry was evenly coated on a copper foil current collector, and the mixture was vacuum dried at 60° C. for 8 hours and compacted to obtain a negative electrode sheet; the area specific capacity of the negative electrode was 3.0 mAh / cm 2 ;

[0093] (3) The diaphragm is a polyethylene / polypropylene (PE / PP) double-layer composite diaphragm with a thickness of 25 μm and a porosity of 40%;

[0094] (4) The electrolyte was 1 M LiPF6 dissolved in a mixed solvent of EC / DMC / EMC (volume ratio 1:1:1), and 2 wt % fluoroethylene carbonate (FEC) was added as an additive;

[0095] (5) Battery assembly: In a glove box with an argon atmosphere, the positive electrode sheet, the separator, and the negative electrode sheet are stacked in sequence, an appropriate amount of electrolyte is injected, and an aluminum-plastic film is used for packaging to prepare a soft-pack battery with a capacity of 2000 mAh;

[0096] (6) Formation and aging: The assembled battery was charged and discharged for the first time at 25°C with a current of 0.1C (formation), and then stored at 45°C for 24 hours for aging.

[0097] The relevant performance tests were conducted on the batteries composed of the negative electrode active materials of the above embodiments and comparative examples. The test structure is shown in Table 1.

[0098] Table 1 Performance of lithium-ion batteries prepared using negative electrode materials in the embodiments of the present invention and comparative examples

[0099]

[0100] It can be seen from the above Examples 1-5 that the lithium-ion battery assembled with the negative electrode material prepared by the technical solution of the present invention has a better first coulombic efficiency and capacity retention rate.

[0101] Comparing Example 1 with Comparative Examples 1-3, the negative electrode materials of Comparative Examples 1-3 do not contain a dopamine layer, a boron-doped graphitized carbon layer and a mixed asphalt carbon layer, respectively, and the first coulombic efficiency and capacity retention rate of the lithium ion batteries of Comparative Examples 1-3 are both reduced, indicating that the multi-layer carbon coating structure provided by the present invention can improve the structural stability and ion transmission capacity of the negative electrode active material through the synergistic effect between the layers.

[0102] By comparing Example 1 with Comparative Example 4, it can be seen that forming a protective layer on the surface of the negative electrode material improves both the initial coulombic efficiency and the capacity retention rate of the lithium-ion battery, especially significantly improves the capacity retention rate.

[0103] By comparing Example 1 with Comparative Examples 5-7, it can be seen that the thickness ratio of the dopamine layer, the boron-doped graphitized carbon layer, and the mixed asphalt carbon layer has an impact on the first coulombic efficiency and capacity retention rate of the lithium-ion battery. Within the thickness range provided by the present invention, the lithium-ion battery can maintain a relatively good first coulombic efficiency and capacity retention rate. When the mixed asphalt layer of Comparative Example 5 is thicker, the first efficiency of the battery is reduced, and the high-temperature cycle surface side reactions are accelerated; when the boron-doped graphitized carbon layer of Comparative Example 6 is thicker, the battery capacity is reduced. This may be because although the boron-doped graphitized carbon layer has good ionic conductivity, its capacity is relatively low, and the increase in thickness will lead to a decrease in capacity; when the dopamine layer of Comparative Example 7 is thicker, the high-temperature storage performance of the battery is reduced. This may be because the residual N and H elements in the dopamine carbon layer will increase the consumption of the electrolyte. Especially under high-temperature storage conditions, excessive consumption of the electrolyte leads to loss of active lithium, resulting in an increase in irreversible capacity.

[0104] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0105] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0106] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A negative electrode active material for a lithium ion battery, characterized in that: include: Nanoporous silicon materials; A first carbon coating layer, which is formed of a conductive carbon material doped with nitrogen and / or sulfur and coated on the nanoporous silicon material, and at least part of the N atoms and / or S atoms in the first carbon coating layer are chemically bonded to at least part of the Si atoms in the nanoporous silicon material at the interface between the first carbon coating layer and the nanoporous silicon material; according to a nanoindentation test method, the binding force between the first carbon coating layer and the nanoporous silicon material at the interface between the two is 15-25 MPa; A second carbon coating layer is formed of a boron-doped graphitized carbon material and coated on the first carbon coating layer; according to Raman spectroscopy, the graphitization degree coefficient of the graphitized carbon material is 0.6 to 0.9; a third carbon coating layer, comprising 30-50 wt% amorphous carbon and 50-70 wt% crystalline carbon, coated on the second carbon coating layer, wherein the amorphous carbon and the crystalline carbon are uniformly mixed and distributed; The protective layer includes one or more of inorganic oxides, inorganic fluorides or LiPON and is coated on the third carbon coating layer.

2. The negative electrode active material for lithium ion battery according to claim 1, characterized in that: The specific surface area of ​​the nanoporous silicon material is 800 to 1200 m 2 / g; And / or, the nanoporous silicon material has a three-dimensional interconnected pore structure, and the pores contained in the three-dimensional interconnected pore structure have a pore size of 10 to 30 nm; And / or, the thickness ratio of the first carbon coating layer, the second carbon coating layer, and the third carbon coating layer is (2-3): (5-10): (5-8); And / or, the thickness of the first carbon coating layer is 2-3 nm, the thickness of the second carbon coating layer is 5-10 nm, and the thickness of the third carbon coating layer is 5-8 nm; And / or, the thickness of the protective layer is 1 to 5 nm; And / or, the median particle size D50 of the negative electrode active material for lithium ion battery is 1 to 10 um.

3. The negative electrode active material for lithium ion battery according to claim 1, characterized in that: The conductive carbon material includes one or more of dopamine, polypyrrole or polythiophene; and / or, the boron doping amount in the second carbon coating layer is 0.2-2wt%; And / or, the third carbon coating layer is formed by carbonizing a mixture of soft asphalt and hard asphalt at 600-1000° C.; And / or, the inorganic oxide includes one or more of A2O3, TiO2, and ZrO2, and the inorganic fluoride includes AF3.

4. The method for preparing the negative electrode active material for lithium ion battery according to any one of claims 1 to 3, characterized in that: include: Using a nitrogen and / or sulfur-doped conductive carbon material to perform liquid-phase carbon coating on a nanoporous silicon material to form a first carbon coating layer on the surface of the nanoporous silicon material to obtain a first intermediate material; Using a gaseous carbon source to perform chemical vapor deposition on the first intermediate material, and introducing a boron source during the chemical vapor deposition process to form a boron-doped graphitized carbon material on the surface of the first carbon coating layer to form a second carbon coating layer, thereby obtaining a second intermediate material; Allowing the surface of the second intermediate material to adsorb a carbon precursor, and carbonizing the second intermediate material adsorbing the carbon precursor to convert the carbon precursor into amorphous carbon and crystalline carbon to form a third carbon coating layer, thereby obtaining a third intermediate material; Atomic layer deposition technology is used to deposit one or more of inorganic oxides, inorganic fluorides or LiPON on the surface of the third intermediate material to form a protective layer, thereby obtaining a negative electrode material for a lithium-ion battery.

5. The preparation method according to claim 4, characterized in that: Specifically include: The nanoporous silicon material is immersed in a solution containing 0.1 to 20 mg / mL of a nitrogen- and / or sulfur-doped conductive carbon material, and reacted at a temperature of 60 to 80° C. for 4 to 8 hours to obtain the first intermediate material; And / or, the nitrogen and / or sulfur-doped conductive carbon material includes one or more of dopamine, polypyrrole or polythiophene.

6. The preparation method according to claim 4, characterized in that: Specifically include: The chemical vapor deposition temperature is 600-1000°C and the time is 2-30h; and / or, the gaseous carbon source comprises acetylene and / or methane; and / or, the boron source comprises triethylboron; And / or, the amount of the boron source introduced is 1 to 5 wt % of the gaseous carbon source.

7. The preparation method according to claim 4, characterized in that: Specifically include: Dispersing the carbon precursor in a solvent to obtain a solution containing 3 to 30 wt % of the carbon precursor, and soaking the second intermediate material in the solution for 12 to 48 hours so that the carbon precursor is adsorbed on the surface of the second intermediate material; The third intermediate material is obtained by carbonizing the obtained product at a temperature of 600 to 1000° C. for 2 to 4 hours.

8. The preparation method according to claim 4 or 7, characterized in that: The carbon precursor includes soft pitch and hard pitch.

9. A negative electrode for a lithium ion battery, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode material for a lithium ion battery according to any one of claims 1 to 3.

10. A lithium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The negative electrode is the negative electrode of the lithium ion battery according to claim 9.

Citation Information

Patent Citations

  • Co-doped silicon-based material and preparation method and application thereof

    CN117810419A

  • Supporting apparatus for upper body

    KR102358634B1

  • Element-doped silicon-carbon composite negative electrode material and preparation method thereof

    US20230369565A1

  • Positive electrode active material, positive electrode sheet, secondary battery, battery module, battery pack and electrical apparatus

    WO2023225838A1